2019
DOI: 10.3390/agronomy9060334
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Study of Crop Evapotranspiration under Canopy Shading

Abstract: California has some of the key agricultural regions in the United States. One of these key regions, San Joaquin Valley, frequently experiences severe droughts leading to shortage of irrigation water. This has a significant impact on the agricultural based economy of the region. It is imperative to develop new strategies to reduce overall water consumption in agriculture without affecting crop yield. A large fraction of irrigation water is lost due to the evapotranspiration (ET) process in the crops and the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…If concrete or any water‐holding structure were built it would be necessary to assess the environmental flow. Further, large cardamom is a shade‐loving crop and shading has an impact on ET requirements; however, productivity improves or remains unaffected (Yu et al, 2019). Further, they mentioned that appropriate partitioning of water usage due to shading will require a number of parameters related to the local climate as well as the crop; selection of an appropriate study with all the required parameters provided is critical.…”
Section: Resultsmentioning
confidence: 99%
“…If concrete or any water‐holding structure were built it would be necessary to assess the environmental flow. Further, large cardamom is a shade‐loving crop and shading has an impact on ET requirements; however, productivity improves or remains unaffected (Yu et al, 2019). Further, they mentioned that appropriate partitioning of water usage due to shading will require a number of parameters related to the local climate as well as the crop; selection of an appropriate study with all the required parameters provided is critical.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of trees over microclimatic conditions and evapotranspiration has been amply studied [62][63][64][65][66]. Benegas et al [67] studied the main processes by which trees influence the soil water dynamics in a tropical grassland, with dispersed trees in Honduras.…”
Section: Particularities Of Ecotypesmentioning
confidence: 99%
“…The findings of this study provide evidence that trees can have positive effects on the local hydric balance. Because it was identified that a large fraction of the irrigation water in crops in central California was lost due to evapotranspiration, Yu et al [63] recommended the use of shade to cover field crops, which resulted in a 37% reduction in evapotranspiration during the hottest months.…”
Section: Particularities Of Ecotypesmentioning
confidence: 99%